Ocatin. A Novel Tuber Storage Protein from the Andean Tuber Crop Oca with Antibacterial and Antifungal Activities - Teresita Flores; Alberto Alape-Girón; Marietta Flores-Díaz; Flores, Hector E. (Plant physiology (Bethesda), 2002)
The most abundant soluble tuber protein from the Andean crop oca (Oxalis tuberosa Mol.), named ocatin, has been purified and characterized. Ocatin accounts for 40% to 60% of the total soluble oca tuber proteins, has an apparent molecular mass of 18 kD and an isoelectric point of 4.8. This protein appears to be found only in tubers and is accumulated only within the cells of the pith and peridermis layers (peel) of the tuber as it develops. Ocatin inhibits the growth of several phytopathogenic bacteria (Agrobacterium tumefaciens, Agrobacterium radiobacter, Serratia marcescens, and Pseudomonas aureofaciens) and fungi (Phytophthora cinnamomi, Fusarium oxysporum, Rhizoctonia solani, and Nectria hematococcus). Ocatin displays substantial amino acid sequence similarity with a widely distributed group of intracellular pathogenesis-related proteins with a hitherto unknown biological function. Our results showed that ocatin serves as a storage protein, has antimicrobial properties, and belongs to the Betv 1/PR-10/MLP protein family. Our findings suggest that an ancient scaffolding protein was recruited in the oca tuber to serve a storage function and that proteins from the Betv 1/PR-10/MLP family might play a role in natural resistance to pathogens.